2020
DOI: 10.1177/2324709620969482
|View full text |Cite
|
Sign up to set email alerts
|

Lung Adenocarcinoma Presenting as Multiple Thromboembolic Events: A Case Report and Review of the Literature

Abstract: Patients with malignancy may present with significant thromboembolic complications including deep vein thrombosis (DVT), pulmonary embolism, arterial thrombosis, nonbacterial thrombotic endocarditis, and stroke due to abnormal coagulation cascades. Although these events are typically recognized later in the disease process, complications of a hypercoagulable state can rarely present as the first manifestation of an occult malignancy. We report a case of a young male who was ultimately found to have an aggressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…It may be speculated that although the imaging does not prove evidence of tumor, these patients may already have reginal lymph nodes or distant organs micrometastasis. In addition, previous researches implied that occult NSCLC often manifests as venous thromboembolism [ 10 , 11 ], which demonstrated that hematogenous metastasis occurred in this kind of NSCLC tumors. Undoubtedly, occult NSCLC had poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It may be speculated that although the imaging does not prove evidence of tumor, these patients may already have reginal lymph nodes or distant organs micrometastasis. In addition, previous researches implied that occult NSCLC often manifests as venous thromboembolism [ 10 , 11 ], which demonstrated that hematogenous metastasis occurred in this kind of NSCLC tumors. Undoubtedly, occult NSCLC had poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, more efficient screen method for example positron emission tomography-computed tomography (PET-CT) might contribute to early detection of primary tumor. Clinicians need to be vigilant when they encounter patients who manifest as internal diseases such as stroke [ 6 , 7 , 8 , 9 ], thromboembolism [ 10 , 11 ] and dermatomyositis [ 12 ]. As occult NSCLC might be the fundamental cause of these non-cancer-related symptoms, the more refined examinations should be performed as soon as possible.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As is true with most neoplasms, lung cancer can have a variety of adverse effects on the body, including hypercoagulability, which can lead to thromboembolic events such as pulmonary emboli (PE), deep vein thrombosis (DVT), ischemic strokes, and non-bacterial thrombotic endocarditis (NBTE) [1][2][3]. Hypercoagulability due to cancer is, in part, due to an imbalance between factors that drive coagulation and fibrinolysis [4].…”
Section: Introductionmentioning
confidence: 99%